Morality, a Necessity for Conflict Resolution in Nigeria: the Islamic Perspective - Yisa Olorunda Balogun (Eastasouth Institute, 2026)
Morality is an indispensable in the modern society. It is through it that the world can record peaceful coexistence. There are positive and negative moralities. Positive morality leads to peaceful coexistence. Negative morality leads to conflict. Conflict resolution is an integral part of every society. Conflict do happen between parents and children, mosques, societies, states, country and the world. Each of the conflict must be resolved if we what peace to reign supreme in Nigeria. The objectives of the write up are to add to the existing literatures on conflict resolution in Nigeria and make people staying away from those things that can lead to conflict. The write up gives the clarification of morality, conflict and resolution, and its methods. Findings revealed that the two dominant religions in Nigeria are Islam and Christianity, constructive and destructive moralities, different resolutions. The negative effects of conflict include fighting, killing/assassination, oppression, suppression, displacement. The settlement of dispute is incumbent upon the Muslim leaders and state functionaries. Our recommendations include that the Muslims should stay away from any kind of killing, discourage it in totality, there should be no discrimination against other religions. However, the tenets of their religion are to be sustained.